2012 Annual Report Conference on Electrical Insulation and Dielectric Phenomena 2012
DOI: 10.1109/ceidp.2012.6378785
|View full text |Cite
|
Sign up to set email alerts
|

A study of how varying degrees of functionalised nanofiller have an effect on nanodielectrics

Abstract: This paper follows our investigation on the interfacial region within nanodielectrics. Fourier Transform Infrared spectroscopy and Raman spectroscopy were used to analyse the effects of modifying nanofiller with coupling agent. Specifically, silane chemistry was used to treat nanosilica samples; by functionalising nanofiller to different degrees and introducing this into an epoxy matrix, a series of nanocomposite systems were prepared and examined. The dispersion state of the treated nanofiller in epoxy was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It was also demonstrated that the use of the electrospinning method reduced the eroded mass fraction of nanofilled microcomposites as compared with the use of the conventional processing method [54]. Reading et al [55], on the other hand, investigated the effect of ultrasonic agitations on the dispersion of montmorillonite and silica nanofillers and found that the breakdown strength of the resulting epoxy nanocomposites improved using this dispersion technique, and this can be ascribed to improved nanofiller dispersion; ultrasonic agitation technique was used also by many other researchers to aid nanoparticle dispersion [56], [57].…”
Section: Nanoparticle Agglomerationmentioning
confidence: 99%
“…It was also demonstrated that the use of the electrospinning method reduced the eroded mass fraction of nanofilled microcomposites as compared with the use of the conventional processing method [54]. Reading et al [55], on the other hand, investigated the effect of ultrasonic agitations on the dispersion of montmorillonite and silica nanofillers and found that the breakdown strength of the resulting epoxy nanocomposites improved using this dispersion technique, and this can be ascribed to improved nanofiller dispersion; ultrasonic agitation technique was used also by many other researchers to aid nanoparticle dispersion [56], [57].…”
Section: Nanoparticle Agglomerationmentioning
confidence: 99%
“…Many studies have tried to modify the surface chemistry of nanoparticles before introducing them into the base polymer and some of these have reported improved electrical properties. However, the underlying mechanisms are not well understood, with different studies referred them to different factors, such as better particle dispersion [4], removal of polar moieties [5] and the introduction of electron traps [6].…”
Section: Introductionmentioning
confidence: 99%